The Potential Role of Halothiobacillus spp. in Sulfur Oxidation and Acid Generation in Circum-Neutral Mine Tailings Reservoirs - Whaley-Martin, Kelly; Jessen, Gerdhard L.; Nelson, Tara Colenbrander; Mori, Jiro F.; Apte, Simon; Jarolimek, Chad; Warren, Lesley A. (Frontiers in Microbiology, 2019)
The biogeochemistry of acid mine drainage (AMD) derived from waste rock associated sulphide mineral oxidation is relatively well characterized and linked to Acidithiobacillus spp.. However, little is understood about the microbial communities and sulphur cycling before AMD develops, key component on its prevention. This study aimed to examine circum-neutral mining impacted water (MIW) communities and its laboratory enrichments for sulphur oxidizing bacteria (SoxBac). MIW in situ microbial communities differed in diversity, structure and relative abundance consistent with site specific variations in total aqueous sulphur concentrations (TotS; ~2 to 17 mM), pH (3.67 – 7.34), and oxygen (22% - 93% saturation). However, the sulphur oxidizer, Halothiobacillus spp. dominated seven of the nine total SoxBac enrichment communities (~76 to ~100% relative abundance), spanning three of the four mines. Indeed, the presence and relative abundance of the identified sixteen known and five unclassified Halothiobacillus spp. here, were the important clustering determinants across parent MIW and enrichment communities. Further, the presence of Halothiobacillus spp. was associated with driving the pH < 4 in enrichment experiments, and the combination of specific Halothiobacillus spp. in the enrichments affected the observed acid to sulphate ratios indicating differential sulphur cycling. Halothiobacillus spp. also dominated the parent communities of the two acidic MIWs providing corroborating evidence for its active role in net acid generation within these waters. These results identify a putative indicator organism specific to mine tailings reservoirs and highlight the need for further study of tailings associated sulphur cycling for better mine management and environmental stewardship.